Perceived Workplace Support for Employee Participation in Workplace Wellness Programs: A Brief Report - Jennifer Altman; Casey Mace Firebaugh; Stephanie M. Morgan; Michael Epstein (Merits, 2023)
Workplace wellness programs have the potential to help improve employee well-being and manage the growing costs associated with poor employee health. Low participation rates stunt the benefits to employee health and limit organizations from maximizing their return on investment. Understanding what influences participation is key to developing effective programs. This research explores the complexity of influencers by blending key concepts of the social–ecologic model and the Fogg Behavioral Model. Ninety-one full-time U.S. employees participated and completed a brief online survey. Key measures included participation in workplace wellness programs, perceived workplace support for health, employee motivation to participate, and employee ability to participate. Perceived support for health was positively correlated with all variables examined. These study findings expand on the current literature to help researchers and practitioners better understand the pathways in which culture of health relates to participation in workplace wellness programs by including the potential moderating effects of motivation, ability, and total number of workplace wellness programs.